Surface engineering glass-metal coatings designed for induction heating of ceramic components - Amir Azam, Khan; Labbé, Jean Claude (IOP Publishing, 2014)
The term Surface Engineering is of relatively recent origin and use, however, the use of coatings and treatments to render surfaces of materials more suitable for certain application or environment is not new. With the advent of Vacuum Technology, Surface Engineering has gained a whole new impetus, whereby expensive materials with adequate mechanical, chemical and thermal properties are being coated or treated on their surfaces in order to achieve what is called as Surface Engineered materials. The present paper presents an overview of recent achievements in Surface Engineering and gives a detailed view of a specific application where glass-metal composite coatings were deposited on ceramic components in order to render them sensitive to induction heating. Sintered glaze coatings containing silver particles in appropriate concentration can be used for the induction heating of porcelain. Mixtures of glass ceramic powders with silver are used to prepare self-transfer patterns, which are deposited over porcelain. Several configurations of these coatings, which are aesthetic to start with, are employed and heating patterns are recorded. The microstructure of these coatings is discussed in relation to the heating ability by a classical household induction system. The results show that this technique is practical and commercially viable.